How do I show that cos(z(adsbygoogle = window.adsbygoogle || []).push({}); _{1}+ z_{2}) = cos(z_{1})cos(z_{2}) - sin(z_{1})sin(z_{2})

I let z_{1}= a + ib & z_{2}= c + id

So cos(z_{1}+ z_{2}) = cos(a+ib+c+id) = cos(a+ib)cos(c+id) - sin(a+ib)sin(c+id) = cos(z_{1})cos(z_{2}) - sin(z_{1})sin(z_{2}). (From the trig identity).

**Physics Forums - The Fusion of Science and Community**

Join Physics Forums Today!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

The friendliest, high quality science and math community on the planet! Everyone who loves science is here!

# How do I show that cos(z1 + z2) = cos(z1)cos(z2) - sin(z1)sin(z2)

Loading...

Similar Threads - show | Date |
---|---|

B How can I show the sum results in this? | Mar 12, 2018 |

I Showing relationship between zeta and gamma | Feb 26, 2018 |

B Wolfram Alpha graph of ln(x) shows as ln(abs(x)) | Oct 14, 2017 |

I What Test to Show that Inverse Curl Exists? | May 11, 2016 |

I Show that a particle moves over a circumference | Mar 7, 2016 |

**Physics Forums - The Fusion of Science and Community**